The Production of Scientific Interpretation Discourse in State Institutions: A Study of Tamsil Language in QS Al-'Ankabūt Verse 41 - Balqis, Ummu Lathifah (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This research departs from the growing tendency of state-affiliated institutions across various parts of the world to engage in the production of Qur’anic interpretations. Through the production of these interpretations, the involvement of state institutions as discourse actors becomes evident, highlighting their role in the contestation of religious authority within Qur’anic exegesis. Therefore, the central focus of this study is to examine how textual structures, cognition, and social context shape the interpretations produced by three state institutions: Tafsir Ilmi by the Indonesian Ministry of Religious Affairs (Kemenag RI), Tafsir al-Muntakhab by the Egyptian Ministry of Religious Affairs, and Tafsir al-Muyassar by the Saudi Ministry of Religious Affairs, particularly regarding the understanding of figurative language in QS Al-‘Ankabūt verse 41. This research is qualitative in nature and employs a library-based study. The primary data consist of the interpretations of QS Al-‘Ankabūt verse 41 from Tafsir Ilmi (Indonesia), Tafsir al-Muntakhab (Egypt), and Tafsir al-Muyassar (Saudi Arabia), analyzed using Teun A. van Dijk’s critical discourse analysis approach. The findings reveal that each institution presents a distinctive exegetical style aligned with its respective state ideology and vision of Islam: Tafsir Ilmi emphasizes the integration of science and religion within a framework of moderate Islam; Tafsir al-Muntakhab conveys religious messages through a rational and educational approach; whereas Tafsir al-Muyassar delivers messages of pure monotheism in a clear and normative manner.